Alemtuzumab: evidence for its potential in relapsing-remitting multiple sclerosis - Brown, William; Coles, Alasdair (Drug design, development and therapy, 2013)
Alemtuzumab (previously known as Campath(®)) is a humanized monoclonal antibody directed against the CD52 antigen on mature lymphocytes that results in lymphopenia and subsequent modification of the immune repertoire. Here we explore evidence for its efficacy and safety in relapsing-remitting multiple sclerosis. One Phase II and two Phase III trials of alemtuzumab versus active comparator (interferon beta-1a) have been reported. Two of these rater-blinded randomized studies assessed clinical and radiological outcomes in treatment-naïve patients; one explored patients who had relapsed despite first-line therapy. Compared to interferon beta-1a, alemtuzumab reduced the relapse rate by 49%-74% (P < 0.0001), and in two studies it reduced the risk of sustained disability accumulation by 42%-71% (P < 0.01). In one study (Comparison of Alemtuzumab and Rebif Efficacy in Multiple Sclerosis; CARE-MS1), there was no significant difference compared to interferon, perhaps reflecting the surprisingly low frequency of disability events in the comparator group. After alemtuzumab, the Expanded Disability Status Scale score improved by 0.14-1.2 points, culminating in a net advantage with alemtuzumab of 0.41-0.77 points over interferon in the CAMMS223 and CARE-MS2 trials (both P < 0.001). Radiological markers of new lesion formation and brain atrophy following alemtuzumab were significantly improved when compared to interferon in all studies. Adverse events were more common following alemtuzumab than interferon beta-1a (7.2-8.66 versus 4.9-5.7 events per person-year). While infusion reactions are the most common, autoimmunity is the most concerning; within Phase III studies, thyroid disorders (17%-18% versus 5%-6%) and immune thrombocytopenic purpura (1% versus 0%) were reported in patients taking alemtuzumab and interferon beta-1a, respectively. All patients responded to conventional therapy. One patient taking alemtuzumab in the Phase II study suffered a fatal intracranial hemorrhage following immune thrombocytopenic purpura, heralding assiduous monitoring of all patients thereafter. Alemtuzumab has been submitted for licensing in relapsing-remitting multiple sclerosis in the United States and Europe.